1994
DOI: 10.1002/mds.870090204
|View full text |Cite
|
Sign up to set email alerts
|

N‐0923, a selective dopamine D2 receptor agonist, is efficacious in rat and monkey models of Parkinson's disease

Abstract: Certain aminotetralins are known to be potent dopamine D2 receptor agonists. N-0923, [-]2-(N-propyl-N-2-thienylethylamino)-5- hydroxytetralin HCl, recognizes the high and low affinity states of the D2 receptor in membranes from bovine caudate with a Klow of 79 nM. The selectivity ratio is D2/D1 = 15 and D2/alpha 2 = 1.4. N-0923 also inhibits dopamine uptake and prolactin secretion, and it is an antagonist at the alpha 2 receptor. N-0923 (3-300 nmol/kg, s.c.) induced dose-dependent contralateral turning behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 14 publications
(4 reference statements)
0
21
0
Order By: Relevance
“…348 Rotigotine is a nonergot, lipid soluble aminotetralin derivative with a strong structural resemblance to dopamine. 349 The drug activates D 3 , D 2 , and D 1 dopamine receptors and has motor benefits in animal models of PD. It has a short halflife when administered by mouth due to extensive first-pass hepatic clearance.…”
Section: Time (Months)mentioning
confidence: 99%
“…348 Rotigotine is a nonergot, lipid soluble aminotetralin derivative with a strong structural resemblance to dopamine. 349 The drug activates D 3 , D 2 , and D 1 dopamine receptors and has motor benefits in animal models of PD. It has a short halflife when administered by mouth due to extensive first-pass hepatic clearance.…”
Section: Time (Months)mentioning
confidence: 99%
“…Rotigotine was effective in a series of preclinical studies in animal models of Parkinson disease. 15,16 Rotigotine is formulated as a transdermal system, a patch, to provide continuous drug delivery that may provide more stable plasma concentrations of a dopaminergic agonist (compared with orally administered drugs) with once-daily dosing for the treatment of patients with early-stage Parkinson disease.…”
mentioning
confidence: 99%
“…The lipophilic nature of rotigotine lends itself to use in a transdermal system [19]. Previous reports of N-0437 refer to a racemic mixture; N-0923 is the (-) enantiomer [20]. (-)-N0437 (rotigotine) is effective in nanomolar concentrations and showed a 150-fold greater potency than (+)-N0437 [21].…”
Section: Pharmacology and Pharmacokineticsmentioning
confidence: 97%
“…In vitro studies with bovine caudate found high affinity equilibrium constants for D 2 and D 1 receptors of 0.3 and 3.0 nmol/l and low affinity constants of 79 and 1160 nmol/l, respectively [20]. Antagonist properties have also been described at α2-adrenergic receptors, with an apparent dissociation constant (K i ) of 110 nmol/l [9,20], a property that distinguishes rotigotine from other D 2 agonists and may reduce the risk of postural hypotension [20]. Rotigotine acts as an agonist at 5HT 1A receptors and displays antidepressant properties in a rat experimental model [20,23].…”
Section: Pharmacology and Pharmacokineticsmentioning
confidence: 97%
See 1 more Smart Citation